2022
DOI: 10.14283/jpad.2022.9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Non-Pharmacological Dementia Prevention Strategies: A Translational Perspective

Abstract: Since developing an effective treatment for Alzheimer’s disease (AD) has been encountered as a challenging task, attempts to prevent cognitive decline by lifestyle modifications have become increasingly appealing. Physical exercise, healthy diet, and cognitive training are all modifiable, non-pharmacological lifestyle factors considered to influence cognitive health. Implementing lifestyle modifications on animal models of AD and cognitive impairment may reveal underlying mechanisms of action by which healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
(179 reference statements)
0
6
0
Order By: Relevance
“…Alanko et al [42 ▪ ] provided a summary of mechanisms of nonpharmacological mainly Alzheimer's disease prevention studies in mice. Indeed, lifestyle interventions in mice have been shown to reduce Alzheimer's disease-related disorder and neuroinflammation and to benefit mitochondrial function, neurogenesis, and cell survival.…”
Section: Current Developments (2020–2022)mentioning
confidence: 99%
“…Alanko et al [42 ▪ ] provided a summary of mechanisms of nonpharmacological mainly Alzheimer's disease prevention studies in mice. Indeed, lifestyle interventions in mice have been shown to reduce Alzheimer's disease-related disorder and neuroinflammation and to benefit mitochondrial function, neurogenesis, and cell survival.…”
Section: Current Developments (2020–2022)mentioning
confidence: 99%
“…Similarly, the Mediterranean diet involves the consumption of fruits, vegetables, whole grains, olive oil, fish, nuts, and legumes and low consumption of processed foods, dairy, and red meat [1] . The Mediterranean diet has shown slowing of neurodegenerative processes including oxidative stress and neuroinflammation which have been associated with improvement in cognitive function, lower rates of cognitive decline, and a reduced risk of Alzheimer’s disease [4] . When both DASH and Mediterranean diets were compared, there were similar rates of slowing cognitive decline in adults [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean diet has shown slowing of neurodegenerative processes including oxidative stress and neuroinflammation which have been associated with improvement in cognitive function, lower rates of cognitive decline, and a reduced risk of Alzheimer’s disease [4] . When both DASH and Mediterranean diets were compared, there were similar rates of slowing cognitive decline in adults [4] . The Mediterranean diet has shown a stronger association with positive cognitive outcomes compared to other specific food groups due to the cumulative beneficial effects of individual ingredients in the diet [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, these initial studies were essential as they laid the foundation for EE as a potential therapy to combat neurodegenerative diseases. Throughout the past decade, many reviews have highlighted the effectiveness of EE against AD pathogenesis [ 31 , 32 , 33 , 34 , 35 , 36 ]. Most notably, it has been shown that EE reversed Aβ pathology as well as reduced senile plaque aggregation in transgenic AD mice [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%